A framework based on location hazard index for optimizing operational performance of emergency response strategies: The case of petrochemical industrial cities. (August 2019) - Rebeeh, Yousuf; Pokharel, Shaligram; Abdella, Galal M.; Hammuda, Abdelmagid
Highlights: Industrial areas with petrochemical installations are prone to industrial hazards. The impact of hazard in each installation depends on the type of materials handled. Hazard index for a location helps to assess response resources in each installation. Integration of index in emergency response model optimizes resource utilization. Abstract: Emergency response operations are very important activities in the industrial areas. As an incident in an industrial area can have considerable economic and social impact, response to such an incident has to be provided in a very short time. Decisions for such responses should consider the available emergency resources, and other factors such as humidity, wind speed, wind direction, population, chemicals, and materials handling, and the characteristics of surrounding affected industrial facilities. In this paper, an index-based emergency response management system (IERMS) is proposed by integrating the location hazard index (LHI) and the response time optimization model. The LHI prioritizes the hazard potential of a location. The response time optimization model provides minimum response time and resource allocations in response to an emergency situation. The use of the framework is illustrated in an industrial city case study by considering petrochemical fire as a demonstration example. The results obtained from the analysis show that the framework is applicable to design the response to incident conditions. It is expected that the framework would help in better resource allocation and efficient response to incidents in industrial areas.